2017
DOI: 10.1515/cclm-2017-0402
|View full text |Cite
|
Sign up to set email alerts
|

Autovalidation and automation of the postanalytical phase of routine hematology and coagulation analyses in a university hospital laboratory

Abstract: Automation allowed optimized laboratory workflow for specific patient populations, thereby ensuring standardized results reporting. Autovalidation of test results proved to be an efficient tool for improvement of laboratory work efficacy and TAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Therefore, it is important to define exactly how the criteria for delta check rule will be defined. Participants of this survey answered that criteria used for delta check were usually obtained by calculation of RCV, and this is consistent with literature data (2,14,21).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Therefore, it is important to define exactly how the criteria for delta check rule will be defined. Participants of this survey answered that criteria used for delta check were usually obtained by calculation of RCV, and this is consistent with literature data (2,14,21).…”
Section: Discussionsupporting
confidence: 85%
“…Once the algorithm is technically set up, decision upon whether all tests or specific test panels will be subject to AV should be made. The results of the survey showed that AV is most commonly applied to routine biochemistry tests, haematology and coagulation tests, and similar results are reported in literature (2,(14)(15)(16)(17). Some studies reported the use of AV for special biochemistry tests, i.e.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Indeed, strengths of humans and computers might be augmented, and weaknesses be offset by each other thus allowing for safe services in high-throughput environments [ 29 , 30 ]. In this sense, not yet widely used autovalidation has the potential to significantly improve on patient safety by more specifically targeting human attention [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%